Social solidarity through food in a society in the eastern Arabian Peninsula In the Abbasid era 247-656 AH / 861-1258 AD - Abdulla, Asma Khaled (Journal of Humanities & Social Sciences, 2024)
The research highlights the role of food in promoting social solidarity in society in the eastern Arabian Peninsula from the beginning of the second Abbasid era until the end of the Abbasid Caliphate at the hands of the Mongols in Baghdad. As one of the most prosperous and civilized eras, many variables emerged in the region, including political, religious, economic, and social, all of which crystallized and formed a unique civilization for us. The research highlights the importance of food as an effective element in building and shaping social relations and achieving social balance between the various groups of society, according to an objective scientific approach, relying on authentic and non-traditional sources and references, at the forefront of which are books on fatwas, jurisprudence, and literature, due to their scientific richness and objectivity. The research addresses important social topics, such as charitable work related to food, which provides support to special groups such as the poor, orphans, the needy, and travelers, whose forms are varied, including bequests, times, and alms, and their nature is varied, including food, cooking utensils, and water resources. The research also dealt with special occasion foods and their role in enhancing cohesion and solidarity between segments of society, in addition to games and entertainment related to food. This confirms the role of food in supporting social solidarity in the region and reveals the prosperity of civilization and the strength of social ties between members of society.